164k views
3 votes
How can parentheses be added to the following equation to make it true?

8 - 3 x 2 - 1 + 1 = 0
Please help...

User MJ X
by
4.7k points

1 Answer

5 votes

Answer:

8 - (3 x 2) - (1 + 1) = 0

or

8 - 3 x 2 - (1 + 1) = 0

Remember PEMDAS.

If I put parenthesis around 3 x 2, I get 6.

But 8 - 6 = 2

How can we make 2 - 1 + 1 = 0?

If we look at PEMDAS, we know (2 - 1) + 1 = 2, but the answer needs to be 0.

So now try 2 - (1 + 1) and that gives me 0.

And it says parentheses...but you can also do 8 - 3 x 2 - (1 + 1) = 0.

User Feng Liu
by
6.5k points